Multifunctional polymer nanocomposites - Leng, Jinsong; Lau, Alan K. T. (Boca Raton, FL. : CRC Press, 2011)
'A broad overview of multifunctional polymer nanocomposites, this book provides a systematic investigation of the topic. It brings to light their importance and the applications they offer. The book also examines new materials from the point of view of architects, interior designers, and designers, encouraging people to examine a new technology more closely, both critically and enthusiastically. This book is quite possibly the first of its kind to provide detailed and systemic progress on polymer nanocomposites from the multifunctional profile'--
Includes bibliographical references and index.
Keywords: Nanocomposites (Materials); Polymeric composites; Smart materials